Makna Dalam Tuturan Sul A’tolo' Pada Perkawinan Masyarakat Desa Nobi-Nobi Kecamatan Amanuban Tengah Kabupaten Timor Tengah Selatan: Indonesia - Mance Alfando Kabnani; Sanhedri Boimau; John Darwis Fallo; Jeff Wilfred Mesah (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
The Sul A'tolo speech is one of the stages of marriage in the Nobi-nobi Village community, Amanuban Tengah District, South Central Timor Regency, where the man's family sends someone to deliver the sul a 'tolo in the form of a package containing jewelry as a sign of engagement to the desired woman. The problem in this study is how the meaning of the sul a'tolo' speech is in the marriage of the Nobi-Nobi Village community, Amanuban Tengah District, South Central Timor Regency. The purpose of this study is to describe the meaning of the sul a 'tolo' speech in the marriage of the Nobi-Nobi Village community, Amanuban Tengah District, South Central Timor Regency. The theory used is the theory of cultural linguistics. This study uses a qualitative descriptive method. In data collection, the researcher used observation, interview, listening, recording and documentation techniques. Based on the results of data analysis, the meaning found in the sul a 'tolo speech is as follows: (1) The meaning of requests and hopes, (2) The meaning of respect and ethics (3) Symbolic and metaphorical meaning, and (4) The meaning of love framed by custom.